PERAN BIMBINGAN DAN KONSELING DALAM PENYELENGGARAAN PENDIDIKAN INKLUSIF - A. Hari Witono (PROGRES PENDIDIKAN, 2020)
Guidance and Counseling (BK) has become a unity in the over all education system. It can be seen from formal education, non-formal and informal education as well. It is also included in the inclusive education model, the service has become a unity and strength in the education system, namely school management-administration and teaching learning process. The three educational services, can be a strength in services to achieve the educational goals. The implementation of BK for inclusive education has a very strategic role for students, namely services for (1) Orientation, (2) Information, (3) Data collection (appraisal), (4) Consultation, (5) (Counseling), and Referral.